2012
DOI: 10.1080/02643294.2012.704354
|View full text |Cite
|
Sign up to set email alerts
|

Routes to short-term memory indexing: Lessons from deaf native users of American Sign Language

Abstract: Models of working memory (WM) have been instrumental in understanding foundational cognitive processes and sources of individual differences. However, current models cannot conclusively explain the consistent group differences between deaf signers and hearing speakers on a number of short-term memory (STM) tasks. Here we take the perspective that these results are not due to a temporal order-processing deficit in deaf individuals, but rather reflect different biases in how different types of memory cues are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 86 publications
3
33
1
Order By: Relevance
“…Th e diff erences between hearing and deaf individuals in terms of decreased digit span as well as increased spatial working memory performance have also been demonstrated in nonnative learners of sign (Capirci, Catt ani, Rossini, & Volterra, 1998;Keehner & Gathercole, 2007). Furthermore, language modality has been shown to bias individuals towards the use of diff erential working memory subcomponents (Hirshorn et al, 2012). Second language learners who are learning another language within the same modality (e.g., EnglishSpanish learners) could show similar working memory capacities barring any quality issues.…”
Section: Wm L2 Acquisition and Modalitymentioning
confidence: 95%
See 4 more Smart Citations
“…Th e diff erences between hearing and deaf individuals in terms of decreased digit span as well as increased spatial working memory performance have also been demonstrated in nonnative learners of sign (Capirci, Catt ani, Rossini, & Volterra, 1998;Keehner & Gathercole, 2007). Furthermore, language modality has been shown to bias individuals towards the use of diff erential working memory subcomponents (Hirshorn et al, 2012). Second language learners who are learning another language within the same modality (e.g., EnglishSpanish learners) could show similar working memory capacities barring any quality issues.…”
Section: Wm L2 Acquisition and Modalitymentioning
confidence: 95%
“…Th e phonological loop is well conceptualized for spoken languages, but how does the phonological loop operate when processing visual languages? Several studies have outlined the working memory system in native deaf signers (Wilson & Emmorey, 1997a, b, 1998Boutla, Supalla, Newport, & Bavelier, 2004;Hall & Bavelier, 2010;Hirshorn, Fernandez, & Bavelier, 2012). Emmorey (1997a,b, and) demonstrated that native deaf signers show similar phonological eff ects (i.e., phonological similarity eff ect, word length effect, articulatory suppression eff ect) for sign language.…”
Section: Wm Language and Modalitymentioning
confidence: 97%
See 3 more Smart Citations